2015
DOI: 10.14319/ijcto.0301.8
|View full text |Cite
|
Sign up to set email alerts
|

Angiomatous nasal polyp: Clinical diagnostic dilemma

Abstract: Angiomatous polyp (Angiectatic nasal polyps) is rare and its incidence is 4-5% of all nasal polyps. As it occurs with variable clinical features and there is no confirmatory preoperative investigation, clinical diagnosis can be a dilemma. Clinical picture of angiofibroma, simple antrochoanal polyp and inverted papilloma may resemble with each other. As polyps invade surrounding bone, these should be distinguished from a malignant mass. We present an interesting case of an infarcted angiectatic nasal polyp with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…However, there is an increasing number of cases that are managed without one depending on the careful preoperative tumour delineation from imaging and on available expertise and experience (4,6,8) . This was supported by a retrospective study in Italy in which surgical experience favours successful endoscopic surgery involving vascular lesions regardless of size (13) . An excellent technique with good endoscopic handling skills does provide satisfactory results as in this case the deviated nasal septum, and spur was first addressed to provide better exposure of margins.…”
Section: Discussionmentioning
confidence: 87%
“…However, there is an increasing number of cases that are managed without one depending on the careful preoperative tumour delineation from imaging and on available expertise and experience (4,6,8) . This was supported by a retrospective study in Italy in which surgical experience favours successful endoscopic surgery involving vascular lesions regardless of size (13) . An excellent technique with good endoscopic handling skills does provide satisfactory results as in this case the deviated nasal septum, and spur was first addressed to provide better exposure of margins.…”
Section: Discussionmentioning
confidence: 87%
“…Chaudhary et al have reported a case of an angiomatous polyp with blood supply from the internal maxillary artery, which could have been detected with contrast-enhanced CT before surgery, with the absence of active bleeding during surgery [ 14 ]. In contrast, Goyal et al have reported that they experienced a large amount of intraoperative blood loss, which required three units of blood transfusion in the case which showed enhancement in CT imaging [ 15 ]. According to these previous reports, angiography and preoperative embolization may not be necessary in all cases, but sometimes well worth considering.…”
Section: Discussionmentioning
confidence: 99%